2006
DOI: 10.1038/sj.embor.7400623
|View full text |Cite
|
Sign up to set email alerts
|

Two internal ribosome entry sites mediate the translation of p53 isoforms

Abstract: The p53 tumour suppressor protein has a crucial role in cell-cycle arrest and apoptosis. Previous reports show that the p53 messenger RNA is translated to produce an amino-terminaldeleted isoform (DN-p53) from an internal initiation codon, which acts as a dominant-negative inhibitor of full-length p53. Here, we show that two internal ribosome entry sites (IRESs) mediate the translation of both full-length and DN-p53 isoforms. The IRES directing the translation of full-length p53 is in the 5 0 -untranslated reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
217
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(236 citation statements)
references
References 23 publications
18
217
0
1
Order By: Relevance
“…p53-null H1299 cells were transfected with luciferase bicistronic constructs containing p53 1-251 RNA in the intercistronic region. 7,8,11 Control cells and glucose-starved cells were harvested 4, 8, 20 and 30 h post-transfection. There was a consistent increase in the relative IRES activity at all these time points following glucose deprivation, with a 1.7-fold increase in activity by 20 h (Figure 1a, H1299 panel and Supplementary Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…p53-null H1299 cells were transfected with luciferase bicistronic constructs containing p53 1-251 RNA in the intercistronic region. 7,8,11 Control cells and glucose-starved cells were harvested 4, 8, 20 and 30 h post-transfection. There was a consistent increase in the relative IRES activity at all these time points following glucose deprivation, with a 1.7-fold increase in activity by 20 h (Figure 1a, H1299 panel and Supplementary Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Dual-luciferase constructs of the p53 (1-251) IRES, first (1-134) IRES, second (135-251) IRESs, 3,8 VEGF and HIF1α IRESs (kind gifts from Professor Greg Goodall, Centre of Cancer Biology, Australia and Professor Annapoorni Rangarajan, MRDG, IISc) and HCV IRES 62 were used in quantitative bicistronic assays. WWP luciferase (a kind gift from Professor Kumaravel Somasundaram, IISc) was used for measuring p53-dependent transactivation, CMV-Renilla-luciferase (Promega, Madison, WI, USA) constructs were used to normalize transfection efficiency.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Insertion of an open-reading frame followed by a hairpin structure in the 5 0 -untranslated region of p53 resulted in an increase in p53/47 synthesis and a decrease in p53, indicating that cap-independent mechanisms of initiation control p53/47 translation via an internal ribosome entry site (IRES) structure located in the region of þ 1 to þ 120 of p53. Hence, the coding region of p53 serves as IRES for p53/47 (Candeias et al, 2006;Ray et al, 2006;Grover et al, 2009). It has also been shown that p53/47 could be generated by alternative splicing (Ghosh et al, 2004), but it should be a rare event as the full-length p53 mRNA was evident after 20 quantitative PCR cycles, whereas the p53/47 message required 40 quantitative PCR cycles, which represents approximately 2 Â 10 20 times less amount of p53/47 mRNA.…”
Section: Introductionmentioning
confidence: 99%
“…The manner in which this 'forced' isoform translation takes place owing to the 5 0 nonsense mutations is unknown and needs further investigation. Previous reports have shown that internal ribosomal entry sites can play a role and can be phase dependent on the cell cycle (Ray et al, 2006b;Grover et al, 2009). Another option might be that translational leakage occurs and 'false' initiation takes place at codon 41, which is surrounded by a Kozak consensus sequence (Kozak, 1984).…”
Section: Discussionmentioning
confidence: 99%